Do Minorities Misrepresent Their Ethnicity to Avoid Discrimination? - Nikoloz Kudashvili; Philipp Lergetporer (Center for Economic Studies and ifo Institute (CESifo), 2019)
Discrimination against minorities is pervasive in many societies, but little is known about minorities' strategies to avoid being discriminated against. In our trust game among 758 high-school students in the country of Georgia, ethnic Georgian trustors discriminate against the ethnic Armenian minority group. We introduce an initial signaling stage to investigate Armenians' willingness to hide their ethnicity to avoid expected discrimination. 43 percent of Armenian trustees untruthfully signal to have a Georgian name. Signaling behavior is driven by expected transfers and non-pecuniary motives. This strategic misrepresentation of ethnicity increases Georgian trustors' expected back transfers and eliminates their discriminatory behavior.
Keywords: C91; C93; D83; J15; J16; D90; 330; discrimination; trust game; experiment; signaling; adolescents